Case Report: Candidate Genes Associated With Prenatal Ultrasound Anomalies in a Fetus With Prenatally Detected 1q23.3q31.2 Deletion - Song, Jiahao; Zhang, Qian; Lu, Bing; Gou, Zhongshan; Wang, Ting; Tang, Hui; Xiang, Jingjing; Jiang, Wei; Deng, Xuedong (Frontiers in Genetics, 2021)
Background: Patients with deletions involving the long arm of chromosome 1 are rare, and the main aim of this study was to refine the genotype-phenotype correlation. Case Report: In this report, a 28-year-old pregnant woman, gravida 2 para 1, at 25+4 weeks of gestation underwent ultrasound examination in our institute. The ultrasonographic findings of the fetus were as follows: (1)fetal growth restriction; (2)cleft lip and palate; (3)bilateral renal hypoplasia; (4)lateral ventriculomegaly; (5)single umbilical artery; (6)absent stomach; (7)coronary sinus dilatation with persistent left superior vena cava, ventricular septal defect and unroofed coronary sinus syndrome. Chromosomal microarray analysis of amniotic fluid from the fetus revealed a 28.025 Mb deletion in 1q23.3q31.2, spanning from position 164,559,675 to 192,584,768(hg19). Conclusion: Genotype-phenotype correlation might improve prenatal diagnosis of fetuses with chromosome 1q deletion. PBX1 could be a candidate gene for fetal growth restriction, renal hypoplasia and congenital heart disease. Fetal growth restriction was accompanied by decreased renal volume in the fetus. Combined with ultrasonic examination, the application of chromosomal microarray analysis will provide accurate prenatal diagnosis.